Pengaruh Pendapatan Asli Daerah dan Investasi terhadap Pertumbuhan Ekonomi dan Tingkat Pengangguran di Provinsi Bali - Suwandika, Putu Eka; Yasa, Nyoman Mahaendra (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 7, Juli 2015 (pp.746 - 872), 2015)
Economic growth is the change in economic conditions of a country towards a better state. The high unemployment may negatively impact on the economy, individuals and communities, and can also cause maximum social welfare is not This study aimed to analyze the effect of directly or indirectly, local revenues and investment to economic growth and the unemployment rate regency / city in the province of Bali in 2008-2012. The data used in this study are secondary data, using the technique of path analysis (path analysis). The results showed, that the regional income has no effect on economic growth and negatively affect the unemployment rate. Investment positive effect on economic growth and does not affect the unemployment rate. Economic growth does not have a significant effect on the unemployment rate. Economic growth is a positive mediating variables in local revenue on the unemployment rate, further economic growth is negative mediating variables in the investment on the unemployment rate.
Keywords: local revenues, investment, economic growth, unemployment